CONTRATACION ELECTRONICA PUBLICA EN COSTA RICA. 2015 Situación actual: decretos ejecutivos Nos. 38830- H- MICITT del 15 de enero; y, 39065-H del 6 de abril, ambos del 2015 - Romero Pérez, Jorge Enrique (2016)
In the year 2015, the Executive Branch enacted two ordinances, in the months of January and April respectively, concerning the matter of electronic or digital public procurement.